Implementation of the Far Eastern Hectare Program: Effect of Incentives to Its Agents - Feoktistova , Ксения Игоревна; Zhuravskaia , Татьяна Николаевна (Economy of Regions, 2023)
The article examines large-scale privatisation of land resources in the Russian Far East under the Far Eastern hectare program. This program transforms the institution of property in the region by transferring land to private ownership. The study explores mechanisms for implementing the program, as well as its effects. New institutional economics is applied to explain the differences in the program implementation rates across regions and municipalities and assess the correlation between reform results and incentives and performance of its agents (mostly municipal authorities). We analysed 155 observations of hectares, a survey of 200 participants of the Far Eastern hectare program, more than 20 interviews with developers, agents and program participants, comparative cases of receiving and not receiving land, participation and non-participation in the program, as well as quantitative statistics on 157,016 granted and non-granted applications for land plots submitted before May 31, 2020. The research revealed an uneven distribution of total applications for land, as well as that of rejections, ranging from 18 % to 56 % per region, with even greater disparity across municipalities. Correlation analysis identified key indicators affecting the share of rejection, including economic indicators of municipalities, as well as indicators of local revenue structure. Regression analysis showed that it is more difficult to get a hectare in economically developed regions, and that the share of granted hectares depends on current or potential benefits of their use for municipalities. It was concluded that economic incentives of municipalities contradict the goals of the Far Eastern hectare program, greatly hindering its successful implementation.